Suppressor genetics reveals novel inter-domain crosstalk within the multidrug transporter Mdr1 protein. Issue 12 (12th April 2022) - Sharma, Suman; Banerjee, Atanu; Moreno, Alexis; Falson, Pierre; Prasad, Rajendra
Abstract : The Multidrug resistance-1 protein (Mdr1p) of Candida albicans is a crucial drug/H+ antiporter within the Major Facilitator Superfamily of proteins involved in the efflux of a broad spectrum of structurally diverse xenobiotic compounds. As a member of the DHA1 subfamily, Mdr1p consists of 12 transmembrane helices (TMHs), divided equally into two Transmembrane Domains (TMDs). How the pseudo-symmetrically positioned TMHs, and the TMDs they compose, communicate with each other remains poorly characterized. In that direction, the recovery of spontaneous chromosomal mutants that negatively affect the primary mutant phenotype can provide essential inter-domain communication insights. For this purpose, in the current study we have performed a suppressor screen for a critically transport deficient mutant G230A, located within TMH-4 of Mdr1p, predicted towards the intracellular space. The recovered suppressor (P528H), that restores the transport capacity of this initially drug susceptible mutant, map to TMH-12, very close to the extracellular space. Since the mutant and suppressor sites occupy the N-domain and C-domain, respectively, and locate at a pseudo-symmetrical position, these results hint to a novel pattern of crosstalk. Additionally, the recovered suppressor mutation restores wild type phenotypes for all tested xenobiotic substrates except cycloheximide, thus implying substrate selectivity. Furthermore, the molecular modeling and docking results suggest a novel compensatory mechanism which is independent of drug binding. Altogether, the present study is a first attempt to gain insights into the transport mechanism of drug/H+ antiporter using the suppressor genetics approach.